Femenina 13 años con Nevus Piloso Gigante - Montoya Mora, Giovanni (2012)
A 13 years-old female patient, without previousmedical conditions. She complained of a gianthairy nevus lesion on her lower back. After 6surgical procedures it is fully resected, with thehelp of tissue expanders.